2010
DOI: 10.1242/jcs.058958
|View full text |Cite
|
Sign up to set email alerts
|

Facioscapulohumeral muscular dystrophy region gene-1 (FRG-1) is an actin-bundling protein associated with muscle-attachment sites

Abstract: SummaryIn vertebrates, overexpression of facioscapulohumeral muscular dystrophy (FSHD) region gene 1 (FRG1) recapitulates the pathophysiology exhibited by FSHD patients, although the role of FRG1 in FSHD remains controversial and no precise function for FRG1 has been described in any organism. To gain insight into the function and potential role of FRG1 in FSHD, we analyzed the highly conserved Caenorhabditis elegans ortholog, frg-1. C. elegans body-wall muscles contain two distinct subcellular pools of FRG-1:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 56 publications
1
56
0
Order By: Relevance
“…Consistent with a putative role in FSHD, several functional studies of the FRG1 protein have shown it to have a role in both angiogenesis and muscle development by utilising quite different biochemical functions, i.e. alternative RNA splicing and actin bundling (Gabellini et al 2006;van Koningsbruggen et al 2007;Hanel et al 2009;Wuebbles et al 2009;Liu et al 2010;Sun et al 2011). Furthermore, a recent analysis of myoblasts isolated from affected muscle of a transgenic mouse overexpressing FRG1 reported a significant loss of cell proliferation and an increased doubling time not observed in unaffected muscle .…”
Section: Epigenetic Mechanisms Involved In Fshdmentioning
confidence: 88%
“…Consistent with a putative role in FSHD, several functional studies of the FRG1 protein have shown it to have a role in both angiogenesis and muscle development by utilising quite different biochemical functions, i.e. alternative RNA splicing and actin bundling (Gabellini et al 2006;van Koningsbruggen et al 2007;Hanel et al 2009;Wuebbles et al 2009;Liu et al 2010;Sun et al 2011). Furthermore, a recent analysis of myoblasts isolated from affected muscle of a transgenic mouse overexpressing FRG1 reported a significant loss of cell proliferation and an increased doubling time not observed in unaffected muscle .…”
Section: Epigenetic Mechanisms Involved In Fshdmentioning
confidence: 88%
“…Therefore, the functional consequence of D4Z4 deletion, like overexpression of an FSHD candidate gene, is the only disease aspect that can be modeled in mice. FRG1 overexpression in mouse, frogs and worms causes an FSHD-like phenotype (Gabellini et al, 2006;Hanel et al, 2009;Liu et al, 2010;Wuebbles et al, 2009). Importantly, we also found a remarkable similarity of the expression profile of FRG1 mice to one of the FSHD patients.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, mice overexpressing FRG1 (FRG1 mice), selectively in the skeletal muscle, display reduced muscle size and develop a muscular dystrophy resembling FSHD (Gabellini et al, 2006). Moreover, studies conducted in Xenopus laevis and Caenorhabditis elegans demonstrated that frg1 is required for normal muscle development and its overexpression causes muscular defects and vascular abnormalities correlated with the clinical findings from FSHD patients Liu et al, 2010;Wuebbles et al, 2009). Collectively, these results suggest that FRG1 is important for muscle function and its aberrant expression could contribute to the FSHD pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…In C. elegans, frg1 protein localized both in nuclei and in the dense bodies that are homologous to vertebrate Z-disk. Interestingly frg1 overexpression in this invertebrate model disrupts the body-wall musculature and the muscular organization (Liu et al, 2010). In Xenopus both knock down and overexpression of frg1 resulted in defective growth and morphogenesis of the myotome indicating that precise levels of frg1 must be maintained for normal muscle morphology (Hanel et al, 2009).…”
Section: Fshd Region Gene 1 (Frg1)mentioning
confidence: 92%
“…Recent studies show the crucial role of FRG1 in maintaining proper muscle structure and function (Hanel et al, 2011;Hanel et al, 2009;Liu et al, 2010). In C. elegans, frg1 protein localized both in nuclei and in the dense bodies that are homologous to vertebrate Z-disk.…”
Section: Fshd Region Gene 1 (Frg1)mentioning
confidence: 99%